Writing a Novella to Introduce Tourism Objects in Palembang - Nurul Aryanti; Murwani Ujihanti; Welly Ardiansyah; Vani Annas Tasya; Vasa Annisa Indina (International Journal of Research in Vocational Studies (IJRVOCAS), 2021)
This research was aimed at knowing how to write a novella entitled “Allied” to promote several tourism destinations in Palembang. In research, the researchers used research and development (R&D) method. The researchers conducted two steps of R&D method: (1) preliminary study, which involved literature study, field study, and product drafting, and (2) model development, which were limited testing and wider testing. The researchers implemented these steps by developing the product. The data were collected from observation and interview in preliminary study step. In model development, the draft of novella regarding the language, structure of sentence, and the content of the story was revised by several experts. The novella was written in English by using Final Draft as the software of writing a story. The story was wrapped in action genre by bringing some mystery in tourism destinations in Palembang that would entertain and educate the readers at the same time. Additionally, in writing a novella entitled “Allied” there were three steps that were conducted with R&D method by Sukmadinata (2015) which the steps were linked to the sixth steps of writing a story by Grenville (2001): Getting Ideas, Choosing, Outlining, Drafting, Revising, and Editing.